Exact Traveling Wave Solutions for the (2+1)-Dimensional ZK-BBM Equation by Exp )) ( ( i i i-Expansion Method (Global Journal of Science Frontier Research, 2014)
In this work, the exp(-Φ(η)) -expansion method is applied to solve the (2+1)dimensional ZK-BBM equation. The traveling wave solutions are expressed in terms of the exponential functions, the hyperbolic functions, the trigonometric functions and the rational functions. The procedure is simple, direct and constructive without the help of a computer algebra system. The exp(-Φ(η)) -expansion method will be used in further works to establish more entirely new solutions for other kinds of nonlinear evolution equations arising in mathematical physics and engineering.
Keywords: the exp(−Φ(η)) -expansion method; the (2 1)-dimensional ZK-BBM equation; complixiton soliton solutions; traveling wave solutions; solitary wave so